Prescribing Patterns in Pediatric General Wards and Their Association with Prescribing Errors: A Retrospective Observational Study - Aylin N. Satir; Miriam Pfiffner; Christoph R. Meier; Angela Caduff Good (Drugs - Real World Outcomes, 2023)
Abstract Purpose There are only limited data on drug utilization patterns in pediatric inpatients, especially on general wards. The aim of the study was to describe prescribing patterns and their associations with prescribing errors in a university children’s hospital in the German-speaking part of Switzerland. Method This was a subanalysis of a retrospective single-center observational study. Patient characteristics and drug use of 489 patients with 2693 drug prescriptions were associated with prescribing errors. Drugs were categorized by the Anatomic Therapeutic Chemical Classification System (ATC), patients were categorized by age group according to European Medicines Agency guidelines, and prescribing errors were analyzed by type [Pharmaceutical Care Network Europe (PCNE) classification] and severity of error [adapted National Coordinating Council for Medication Error Reporting (NCC MERP) index]. Results The most frequently prescribed ATC classes were nervous system (N) (42.6%), alimentary system (A) (15.6%), and anti-infective drugs (J) (10.7%). Eighty-two percent of patients were prescribed an analgesic. Most drugs were prescribed for oral (47%) or intravenous (32%) administration, but the rectal route was also frequent (10%). The most frequently prescribed drugs were paracetamol, metamizole, and ibuprofen. The high number of metamizole prescriptions (37% of patients were prescribed metamizole) is typical for German-speaking countries. Older pediatric patients were prescribed more drugs than younger patients. A statistically significant difference was found in the rate of potentially harmful errors across age groups and for gender; children between 2 and 11 years had a higher rate of potentially harmful errors than infants under 2 years (p = 0.029) and female patients had a higher rate of potentially harmful errors than male patients (p = 0.023). Recurring errors were encountered with certain drugs (nalbuphine, cefazolin). Conclusions Our study provides insight into prescribing patterns on pediatric general wards in a university children’s hospital in Switzerland and highlights some areas for future research. Especially, the higher risk for prescribing errors among female pediatric patients needs further investigation.